Tax Compliance and Its Determinants: A Study on Small and Medium Enterprises (SMEs) - Abiola Okunola; Fola Alabi (International Journal of Economics, Management and Accounting, 2024)
This study explores the determinants of tax compliance among Small and Medium Enterprises (SMEs), focusing on factors such as financial literacy, regulatory environment, and perceived fairness of the tax system. Through a survey of SMEs across various industries, the research reveals that higher levels of financial literacy and a supportive regulatory environment encourage tax compliance. The study offers recommendations for policymakers to improve tax compliance rates among SMEs.